2009
DOI: 10.1088/0957-4484/20/22/225602
|View full text |Cite
|
Sign up to set email alerts
|

The anodization voltage influence on the properties of TiO2nanotubes grown by electrochemical oxidation

Abstract: A systematic study of titanium dioxide (TiO2) nanotubes (NTs) grown by electrochemical anodization in NH4F + glycerol electrolyte has been carried out in a broad range of anodization voltage of 5-350 V and acid concentration of 0.1-0.7 wt%. It is found that NTs can be grown in the voltage range from 10 to 240 V. The maximum NH4F acid concentration at which NTs can be formed decreases with the anodization voltage (V(a)). The maximum NH4F acid concentration is 0.7% for V(a)<60 V, and it decreases to 0.1% at V(a)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…By anodic oxidation at 100-200 V, performed for 6 hours in 0.15% solution of NH 4 F in glycerol [10], it was later found by SEM that film was obtained instead of NTs. TiO 2 film electrodes were not subjected to further investigation.…”
Section: Materials Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…By anodic oxidation at 100-200 V, performed for 6 hours in 0.15% solution of NH 4 F in glycerol [10], it was later found by SEM that film was obtained instead of NTs. TiO 2 film electrodes were not subjected to further investigation.…”
Section: Materials Preparationmentioning
confidence: 99%
“…Secondly, they showed that by using non-aqueous electrolytes smooth NTs without sidewalls inhomogeneity and the improved ordering could be obtained [9]. TiO 2 NTAs may be obtained by anodization in non-aqueous electrolytes containing 0.1-1 wt % of fluoride ions at the constant voltage between 5-150V [1] or even up to 350 V [10].…”
Section: Introductionmentioning
confidence: 99%
“…A lower temperature will not provide enough thermal energy for large crystalline size, while a higher temperature will lead to rutile phase. Based on glancing angle X-ray diffraction (GAXRD) characterization, crystallization process requires the annealing temperature exceeding 300 C. 23 Figure 4 presents GAXRD results for TiO 2 NTs annealed at 450 C for 30 min in air ambient. The typical peaks (101) and (004) of anatase phase can be obviously detected at 2 = 25 3 and 2 = 37 8 along with other anatase peaks of (200), (105) and (211) indicating a good crystallization.…”
Section: Reactionmentioning
confidence: 99%
“…Since Zwillig et al reported about growth of porous titania layers by electrolytic anodisation back in 19991 and Gong et al2 as well as Beranek et al3 described synthesis of titania nanotubes by anodic oxidation in a hydrofluoric electrolyte, the latter have attracted tremendous interest in a broad range of areas, including dye‐sensitized solar cells, hydrogen production, photocatalysis, functional biomaterials and – last but not least – medical coatings 4. While since then numerous alternative approaches for synthesis have emerged,4, 5 including sol‐gel techniques, metal‐organic physical vapor deposition and seeded growth, anodization has also undergone continuous development within at least four generations of synthesis (Refs. 6–9 and references therein), which allow for cost‐effective self‐organized synthesis of very regular nanotube arrays with highly flexible tube diameters, wall thicknesses and lengths over macroscopic scales by well‐controllable modifications of the electrochemical conditions.…”
Section: Desorption Times τ1 and τ2 For Samples Exposed To Air And mentioning
confidence: 99%